VD_FINDINFO HC / 2013 / 471 vom 3. Juli 2013 - VD Tribunal cantonal (2013)
CURATELLE ÉDUCATIVE, PERPETUATIO FORI | 176 al. 3 CC, 308 al. 1 CC, 308 al. 2 CC, 308 al. 1 let. b CPC (CH), 312 al. 1 CPC (CH)